Diaclean Pera Sterilant, a high-level disinfectant product, by UMP - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2020)
KUANTAN: A team of researchers from Universiti Malaysia Pahang (UMP) have produced their very own environment-friendly disinfectant made from vinegar (food-grade acetic acid) to help battle the Covid-19 pandemic.